Resisting and Remaking the Smart City and the ‘Internet of Things’ - Forlano, Laura (AoIR Selected Papers of Internet Research, 2013)
Current discussions about urban media and technologies such as smart cities and the “internet of things” reinforce a corporate vision that is based on values of efficiency, productivity, innovation and security, which has been embraced by government stakeholders. Advocates of open technologies, on the other hand, reinforce civic values such as privacy, openness and transparency. Yet, both interpretations often bolster technologically deterministic views about the revolutionary potential of information technology. Specifically, with respect to smart cities and the “internet of things,” discussions often focus on the potential of ubiquitous and invisible computers with “anytime, anywhere” access to the Internet. These popular framings are important sites of appropriation and resistance because they greatly shape our imaginations of the opportunities and constraints of urban technologies. This paper seeks to address the considerable gaps between the discourses around these technologies with the empirical lived experience based on media representations, speculative and critical design interventions and field studies.